2022
DOI: 10.3390/cells11030563
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Preferentially Promotes Necroptosis of Lung Epithelial Cells by Upregulating MLKL

Abstract: Necroptosis, a form of programmed lytic cell death, has emerged as a driving factor in the pathogenesis of acute lung injury (ALI). As ALI is often associated with a cytokine storm, we determined whether pro-inflammatory cytokines modulate the susceptibility of lung cells to necroptosis and which mediators dominate to control necroptosis. In this study, we pretreated/primed mouse primary lung epithelial and endothelial cells with various inflammatory mediators and assessed cell type-dependent responses to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…In normal lung tissue, low TLR4 expression ensures a controlled state of inflammation. In Contrast, in Spn-infected patients, increased expression of TLR4 is sustained, resulting in inappropriate signaling by lung epithelial cells to LPS, through activating various molecules including MyD88, which ultimately activates the NF-κB signaling pathway and boosts the excessive release of TNF-α and other pro-inflammatory cytokines, resulting in the blood-gas barrier damage and lung epithelial cell apoptosis ( Aboudounya and Heads, 2021 ; Tang et al., 2021 ; Hao et al., 2022 ). In this study, as the serum levels of pro-inflammatory cytokines and endotoxin were increased, the expressions of ZO-1, Claudin 5 and Occludin in the lung tissues of Spn-infected mice were significantly decreased while TLR4, p38 and NF-κB were increased.…”
Section: Discussionmentioning
confidence: 99%
“…In normal lung tissue, low TLR4 expression ensures a controlled state of inflammation. In Contrast, in Spn-infected patients, increased expression of TLR4 is sustained, resulting in inappropriate signaling by lung epithelial cells to LPS, through activating various molecules including MyD88, which ultimately activates the NF-κB signaling pathway and boosts the excessive release of TNF-α and other pro-inflammatory cytokines, resulting in the blood-gas barrier damage and lung epithelial cell apoptosis ( Aboudounya and Heads, 2021 ; Tang et al., 2021 ; Hao et al., 2022 ). In this study, as the serum levels of pro-inflammatory cytokines and endotoxin were increased, the expressions of ZO-1, Claudin 5 and Occludin in the lung tissues of Spn-infected mice were significantly decreased while TLR4, p38 and NF-κB were increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, IFN-γ is a very dangerous double-edged sword, because IFN-γ can also induce severe damage to airway epithelial cells and pneumocytes, including cellular death [ 40 , 41 ]. One study identified an interferon (IFN)-γ-regulated subset of monocytes, CCR2 + monocytes, as a major cause of acute lung injury (ALI) during influenza A (IAV) virus infections, where IFN-γ regulated the recruitment of the inflammatory phenotype of CCR2 + monocytes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T-cells were the main sources of IFN-γ in IAV-infected lungs, and IFN-γ had a signaling role in the regulation of CCR2 + monocyte-mediated lung pathology during IAV infections [ 40 ]. Furthermore, IFN-γ not only attracts lung damaging, inflammatory monocytes, IFN-γ can also cause pneumocyte death by necroptosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…During influenza virus infection, the monocytes/macrophages are recruited from the cycle into the damaged areas of lung tissues to repair the injury and clear the virus, producing and releasing a variety of factors, including proinflammatory cytokines (TNF- α , IL-1 β , and IL-6), antiviral cytokines (IFN- α / γ ) and chemokines (MCP-1), which are directly or indirectly involved in the antiviral response. The immune response induced by these mediators is beneficial to the organism, but if induced excessively, it can be transformed into an immunopathological response, causing destruction of self-cells and inflammatory damage to lung tissues [ 5 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…e immune response induced by these mediators is beneficial to the organism, but if induced excessively, it can be transformed into an immunopathological response, causing destruction of self-cells and inflammatory damage to lung tissues [5,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%